2006
DOI: 10.1038/sj.bmt.1705514
|View full text |Cite
|
Sign up to set email alerts
|

Autologous stem cell transplantation beyond 60 years of age

Abstract: Along with improved supportive care and thus reduced treatment-related mortality, an increasing number of elderly patients (460 years) with haematological malignancies are now considered for high-dose therapy (HDT) supported by autologous stem cell transplantation (ASCT). ASCT is feasible in selected elderly patients with multiple myeloma and those with non-Hodgkin's lymphoma. As elderly patients have generally been excluded from randomized studies evaluating efficacy of ASCT in comparison with non-transplant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 67 publications
1
12
0
Order By: Relevance
“…The finding of patient age as a significant risk factor is in agreement with Badros et al, who reported an increase in risk by 9% with each decade of life [12]. These authors interpreted this as a reflection of longer durations of bisphosphonate therapy although it is possible that changes in bone metabolism in the elderly may be an additional factor [12,18].…”
Section: Discussionsupporting
confidence: 81%
“…The finding of patient age as a significant risk factor is in agreement with Badros et al, who reported an increase in risk by 9% with each decade of life [12]. These authors interpreted this as a reflection of longer durations of bisphosphonate therapy although it is possible that changes in bone metabolism in the elderly may be an additional factor [12,18].…”
Section: Discussionsupporting
confidence: 81%
“…25 Advanced age is an independent risk factor for recurrent NHL; thus a higher percentage of older patients will be candidates for autologous SCT. 10 Advances in supportive care such as the introduction of peripheral blood stem cell grafts, growth factors, antibiotic prophylaxis, transfusion support and mucositis prevention have reduced the toxicity of transplantation. There are no conclusive data to recommend one conditioning regimen over another in this population.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Several conditioning regimens for SCT have been described in older patients with NHL. 7,8,10 The BEAM regimen incorporates carmustine, etoposide, cytarabine and melphalan and has been associated with a treatmentrelated mortality of 9% in older patients. 9 CY, BCNU and etoposide has also been extensively used and is associated with cardiac toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…There may be ways to improve this. 26 In addition to patient selection, the conditioning regimen also appears to be important. Regimens based on total body irradiation have conventionally been used cautiously in elderly patients, which was also apparent in this registry analysis.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%